Daily School Physical Activity Improves Academic Performance - Jesper Fritz; Marcus E. Cöster; Björn E. Rosengren; Caroline Karlsson; Magnus K. Karlsson (MDPI AG, 2020)
Physical activity (PA) may improve brain development, cognition, concentration and academic performance. In this prospective controlled intervention study, we increased the level of PA in 338 children aged 6-8 years at study start, from the Swedish standard of 60 min per week to 200 min per week (40 min daily). The intervention continued in all nine compulsory school years until the students graduated between 2007-2012. All other 689,881 Swedish children who graduated the same years were included as a control group. We registered at graduation eligibility rate for upper secondary school and the final grade score (from 0 to 320 grade points). We also registered the same end points in the 295 students in the index school and in all other 471,926 Swedish students who graduated in 2003-2006, that is, those who graduated before the intervention study started. Before the intervention, academic performance was similar among children in the index school as for all other Swedish boys and girls. With the intervention, the eligibility rate increased for boys in the index school by 7.3 percentage points and the mean grade scores by 13.3 points. This should be compared with a decrease of 0.8 percentage points in eligibility rate and an increase by 2.7 points in grade score in other Swedish boys. No changes were seen for intervention girls, neither in eligibility rates or grade scores. By introducing daily school-based PA in compulsory school, more boys would probably reach the eligibility rate for higher education.